ICT Gymkana - Blázquez Barrantes, Fco. José (Pulso. Revista de educación, 2015)
The ICT Adventure is an intrepid experience where students are given the opportunity to learn in groups through the use of ICT and focusing on multiple intelligences. We created this adventure to reinforce and strengthen students’ knowledge of fractions. Students worked with tablets and apps to decipher QR codes. These codes contained mathematical problems which had to be solved in cooperative groups. On finishing each activity, groups were guided to the following clue which contained a new QR code to be resolved. The activity was evaluated with an app called Kahoot. Through this app we evaluated the efficacy and results of the activity.
Keywords: Pedagogical innovation; Multiple intelligences; Cooperative learning; Apps; QR codes